An anti-inflammatory transcriptional cascade conserved from flies to humans. - Pavlidaki, A.; Panic, R.; Monticelli, S.; Riet, C.; Yuasa, Y.; Cattenoz, P.B.; Nait-Oumesmar, B.; Giangrande, A. (Cell reports, 2022)
Innate immunity is an ancestral process that can induce pro- and anti-inflammatory states. A major challenge is to characterize transcriptional cascades that modulate the response to inflammation. Since the Drosophila glial cells missing (Gcm) transcription factor has an anti-inflammatory role, we explored its regulation and evolutionary conservation. Here, we show that the murine Gcm2 (mGcm2) gene is expressed in a subpopulation of aged microglia (chronic inflammation) and upon lysophosphatidylcholine (LPC)-induced central nervous system (CNS) demyelination (acute inflammation). Moreover, mGcm2 conditional knockout mice show an increased inflammatory phenotype upon aging or LPC injection, and hGCM2 is expressed in active demyelinating lesions of patients with multiple sclerosis. Finally, Drosophila Gcm expression is induced upon aging and acute challenge, and its overexpression decreases the inflammatory phenotype. Altogether, these data indicate that the inducible Gcm cascade is conserved from flies to humans and represents a potential therapeutic target in the control of the inflammatory response.